The Sony Smart Tennis Sensor accurately measures external workload in junior tennis players. Issue 1 (February 2019) - Myers, NL; Kibler, WB; Axtell, AH; Uhl, TL
This study determined the measurement accuracy of the Sony Smart Tennis Sensor (SSTS) when categorizing hitting volume, shot type, and ball speed, and to determine the average number of shots performed by junior players during practice and match play. Fourteen high school players (16 ± 3 years, 12 males, 2 females) were followed for a period of six weeks. Criterion validity was established by comparing video and observational data to the SSTS data in order to determine the hitting volume, stroke type, and ball speed measurement accuracy of the sensor. Additionally, each player's hitting volume and stroke type were tracked for six weeks using the SSTS. Strokes were categorized into forehand swings, backhand swings, overhead swings, and total volume. Hitting volume accuracy ranged between 91% and 96% for all forehand, backhand, and overhead swings. All backhand and overhead swings were identified correctly by the SSTS when compared to visual observation. There was a 10% error rate in forehand swing shot identification. Approximately 50%, 30%, and 20% of the total volume of strokes are FHs, BHs, and serves, respectively, regardless of practice or match play. The SSTS is an accurate way of measuring hitting volume in tennis and can be used by coaches to track practice and match volume over time. Monitoring workloads over time can help prepare players for rigorous competition schedules.